Analysis of Factors Determining Serologic Response to Treatment of Early Syphilis in Adult Men - Justyna Czarny; Damian Kadylak; Małgorzata Sokołowska-Wojdyło; Roman J. Nowicki (Infectious Disease Reports, 2025)
Background: Syphilis is an infectious systemic disease that remains a public health threat, with an increasing incidence worldwide. Despite the availability of diagnostic tests and effective treatments, achieving a serological cure remains challenging for some patients. Methods: A retrospective cohort study of 130 male patients with early syphilis who attended the Department of Dermatology Venereology and Allergology in Gdansk was carried out between 2021 and 2024. This study assessed the rates of proper serological response and seroreversion of the VDRL test during the posttreatment follow-up period and analyzed selected factors influencing the achievement of these points. Results: The treatment outcomes were favorable; 96.15% of the patients achieved a proper serological response at a median of 1.54 months and seroreversion of the VDRL test within 18 months (median time = 7 months). A significantly greater proper serological response was observed in the primary and secondary syphilis patients than in the early latent syphilis patients (p = 0.005). A proper serological response was associated with age over 30 years (risk ratio (RR) = 1.381, p = 0.008) and VDRL baseline titers (≥1:32) (RR = 1.484, p = 0.005). The patients in the secondary or latent stage of early syphilis had a lower risk of seroreversion than those in the primary stage did (RR = 0.590, p = 0.030; RR = 0.560, p = 0.019, respectively). High titers at baseline (≥1:32) were also associated with a 30.8% reduced risk of seroreversion compared with lower titers (RR = 0.692, p = 0.038). Conclusions: These results suggest that age, syphilis stage, and titer level are significant predictors of the response rate. Based on these results, it is recommended that serological follow-up be concentrated within the first three months posttreatment, as this period accounts for the majority of treatment responses.